ARTIFICIAL INTELLIGENCE ITS IMPORTANCE IN HUMAN LIFE AND ACTIVITY - Saparov Orinbasar Bakhievich (Web of Journals Publishing, 2024)
This article talks about the importance of artificial intelligence in our daily life, how it affects us and its benefits, its various functions and its benefits in education.
Keywords: Artificial intelligence, virtual assistants, content creation, individual training.